Theatre artisans and their craft : the allied arts fields - Jaen, Rafael; Durbin, Holly Poe; Essin, Christin (Backstage, 2020)
"Theatre Artisans and Their Craft: The Allied Arts Fields profiles fourteen remarkable artists and technicians who elevate theatre production to new dimensions, explore new materials and technologies, and introduce new safety standards and solutions. Readers will learn how the featured artists delved into entrepreneurial ventures and created their own work for themselves; researching, studying, and experimenting, seeking answers when none were available. The book explores how to make an impact in the entertainment industry from behind the scenes, and how students can model themselves after these successful professionals to jump-start their career in theatre production. Aimed at theatre and film practitioners in the allied arts fields, Theatre Artisans and Their Craft offers a collection of success stories that are both inspiring and informative"--